An Analysis of Work Stress and Family-Conflict Work on Organizational Commitment and Turnover Intention: A Case Study on Employee of PT. Apparel One Indonesia - Junaidi, Achmad; Elsa Adelia, Febri; Nindhita, Yoga (SCAD Independent, 2022)
This study departs from findings that show that the turnover rate of employees at PT. Apparel One Indonesia in 2018 is 3.715% which exceeds the threshold set by the company by 2% each year, and the findings that the variables that explain the phenomenon of turnover intention are still different which then leads to the formulation of the problem regarding